Trans-Anastomotic Drainage Tube Placement After Hand-Sewn Anastomosis in Patients Undergoing Intersphincteric Resection for Low Rectal Cancer: An Alternative Drainage Method - Zhong, Xinjian; Xie, Xiaoyu; Hu, Hang; Li, Yi; Tian, Shunhua; Qian, Qun; Jiang, Congqing; Ren, Xianghai (Frontiers in Oncology, 2022)
Anastomotic leakage (AL) is a common complication after intersphincteric resection (ISR). It significantly reduces quality of life and causes great distress to patients. Although traditional drainage (e.g., anal and pelvic catheters) may reduce the impact of AL to some extent, their role in reducing the incidence of AL remains controversial. In this study, we developed a novel drainage technique involving the placement of drainage tubes through the gap between sutures during handsewn anastomosis, to reduce the occurrence of anastomotic leakage. We retrospectively analyzed 34 consecutive patients who underwent intersphincteric resection requiring handsewn anastomosis between February 1, 2017, and January 1, 2021. Patients were classified into the trans-anastomotic drainage tube group (TADT, n = 14) and the non-TADT group (n = 20) based on whether trans-anastomotic tube placement was performed. The incidence of postoperative complications, such as AL, was compared between the two groups, and anal function of patients at 1-year post-ISR was evaluated. Six cases of AL occurred in the non-TADT group, while none occurred in the TADT group; this difference was statistically significant (p=0.031). The TADT group also had a shorter hospital stay (p=0.007). There were no other significant intergroup differences in operation time, blood loss, pain score, anastomotic stenosis, intestinal obstruction, or incidence of wound infection. In the 30 patients (88.2%) evaluated for anal function, there were no significant intergroup differences in stool frequency, urgency, daytime/nocturnal soiling, Wexner incontinence score, or Kirwan grading. Taken together, trans-anastomotic tube placement is a novel drainage method that may reduce AL after ISR requiring handsewn anastomosis and without adversely affecting anal function.